Origin of the Proton-transfer Step in the Cofactor-free (1H)-3-Hydroxy-4-oxoquinaldine 2,4-Dioxygenase - Hernandez-Ortega, Aitor; Quesne, Matthew G.; Bui, Soi; Heuts, Dominic P.H.M.; Steiner, Roberto A.; Heyes, Derren J.; de Visser, Sam P.; Scrutton, Nigel S. (The Journal of biological chemistry, 2014)
Dioxygenases catalyze a diverse range of chemical reactions that involve the incorporation of oxygen into a substrate and typically use a transition metal or organic cofactor for reaction. Bacterial (1H)-3-hydroxy-4-oxoquinaldine 2,4-dioxygenase (HOD) belongs to a class of oxygenases able to catalyze this energetically unfavorable reaction without any cofactor. In the quinaldine metabolic pathway, HOD breaks down its natural N-heteroaromatic substrate using a mechanism that is still incompletely understood. Experimental and computational approaches were combined to study the initial step of the catalytic cycle. We have investigated the role of the active site His-251/Asp-126 dyad, proposed to be involved in substrate hydroxyl group deprotonation, a critical requirement for subsequent oxygen reaction. The pH profiles obtained under steady-state conditions for the H251A and D126A variants show a strong pH effect on their kcat and kcat/Km constants, with a decrease in kcat/Km of 5500- and 9-fold at pH 10.5, respectively. Substrate deprotonation studies under transient-state conditions show that this step is not rate-limiting and yield a pKa value of ∼7.2 for WT HOD. A large solvent isotope effect was found, and the pKa value was shifted to ∼8.3 in D2O. Crystallographic and computational studies reveal that the mutations have a minor effect on substrate positioning. Computational work shows that both His-251 and Asp-126 are essential for the proton transfer driving force of the initial reaction. This multidisciplinary study offers unambiguous support to the view that substrate deprotonation, driven by the His/Asp dyad, is an essential requirement for its activation. Background: The mechanism of cofactor-free dioxygenases has not been clearly elucidated. Results: Mutation of the His/Asp dyad in (1H)-3-hydroxy-4-oxoquinaldine 2,4-dioxygenase strongly affects substrate deprotonation and overall catalysis. Conclusion: Base mechanism is demonstrated where His-251 acts as catalytic base and Asp-126 modulates basicity. Significance: Many dioxygenases activate their substrates via deprotonation, which is an essential step for later reaction with oxygen.